Environment-friendly agent [SG101] for the Control of Common Scab on Potato - Tsror (Lahkim), Leah; Hazanovsky, Marina; Lavee, M; Ben-Yehuda, Nimrod; Zig, Uri (MTT, 2007)
Common scab on potato, caused by Streptomyces spp., can result in severe damage to pota-toes. The increased prevalence of this disease in Israel, especially in Ma'on region (South-West Israel), is attributable to several factors, among which are: susceptible crops such as peanuts and radish being grown in short rotations, soils that are conducive to the disease, and the absence of effective eradication methods. Contaminated potato seed tubers are the major means of spreading the pathogen. Seed borne inoculum arrives through certified seed lots imported from Northern-Europe for the spring. In average 26% of the seed lots were contaminated with intermediate and high levels of common scab between 2004 and 2007.However, so far any of the tested seed treatments was efficient in reducing the disease incidence or severity. The primary inoculum source of Sreptomyces is seed tubers. Once the pathogen is introduced and established into the soil, it survives for a long time, and only a radical soil fumigation (such as formaldehyde) can reduce the pathogen levels. The objective of the present study was to evaluate SG101, a stabilized formulation of hy-drogen peroxide agent (3.5-7% H2O2) as a seed treatment for controlling common scab on potatoes. Seed tubers (cv. Desiree) highly contaminated with common scab were treated with SG101 or Bactoril (Quat Ammonium) by a low volume spray, and mancozeb by dusting. Two experiments arranged in a randomized complete block design, with four replications were planted in two sites (Gilat -loess soil and Halutza - sandy soil). In Gilat, the incidence of progeny tubers with russet scab was significantly reduced in both SG101 and mancozeb treatments. In Halutza, the incidence of russet and common scab were significantly lowerin SG101, compared with the control and Bactoril. mancozeb treatment.The findings in this study indicate the high potential of using SG101 as a seed treatment for controlling scab in the short-term (in the harvested progeny). Furthermore, because of this SG101 efficiency, an advantage for the long-term is being achieved, by preventing the spread of the pathogen and infestation of soils. Additional studies on the potential use of SG101 as a furrow treatment and its effect on other seed-borne pathogens are being currently conducted.
Keywords: Ka; Streptomyces; common scab; seed treatment